(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Trifonova N.S. Keywords: listening comprehension, input, spoken text, acoustic signal, linear and real-time nature, linguistic features. The crucial factor which makes listening comprehension unique is the fact that the external input for the listener is presented as an oral text. Without understanding the input adequately any communication fails. The article focuses on the analysis of some core properties and essential characteristics of a spoken text for listening comprehension, namely: the oral text is encoded as an acoustic signal, it is linear and takes place in real time and it possesses the linguistic features which are specific for the oral speech composition, construction and presentation.